(untitled) (Journal of Hama University, 2019)
The experiment is done on 24 Friesian calves with similar weights between 150-175 kg. The study aimed to know the effect of magnetically treated water in protein digestion coefficient. Experimental animals were randomly distributed among three groups with 8 calves in each group. All experimental animals were fed on one diet and the first group calves (control group) were provided with normal drinking water that was not magnetically treated, while the second and third group calves were provided with different Magnetic Field 1000 / 2000Gauss in a series. This study lasted six months in which crude protein was analyzed in feed which was given to all groups. Analysis of undigested protein was done in manure in all groups. In addition to the weight of calves in the experimental groups and estimate the total and daily increase in weight The water which was used in all the groups was analyzed. Water analysis results showed a change in the properties of the water Which was clear that water alkalinity increased (height of PH number) The second group calves gained significace in the other groups at the level (P≤ 0.05) in the total weight raise which was (171 kg) followed by the third and first group calves 147.4 - 168.8 in a series. In addition, the second group calves gained significace in the other groups at the level (P≤ 0.05) with an average daily raise 950 g / a day) followed by the third and first group calves 819 – 938 g in a series. The results showed a significant increase (P≤ 0.05) for the digestion of protein intake in the second group 70.4% followed by calves of the third group 69.6% and digestion of the protein in the control group was 67.76%.